Cytosolic Ca2+ buffering determines the intra-SR Ca2+ concentration at which cardiac Ca2+ sparks terminate. Issue 3 (September 2015) - Bovo, Elisa; Mazurek, Stefan R.; Fill, Michael; Zima, Aleksey V.
Graphical abstract